Service Accessibility and Wellbeing in Amman’s Neighborhoods: A Comparative Study of Abdoun Al-Janoubi and Al-Zahra - Majd Al-Homoud; Reema Aldahody (Buildings, 2025)
Amman, the capital of Jordan, has undergone significant urbanization over the past seventy years, evolving from a small village into the nation’s largest city. This rapid growth has led to unpredictable population increases, creating socioeconomic disparities and affecting residents’ access to services and overall wellbeing. This study investigates the impact of service accessibility on wellbeing in two neighborhoods of Amman: Abdoun Al-Janoubi and Al-Zahra. Data were gathered from 492 household heads through structured interviews and systematic sampling. The study analyzed accessibility factors such as safety, convenience, comfort, and esthetics, and their influence on residents’ wellbeing, defined by positive emotions, social relationships, and overall life meaning. The results indicate a robust correlation between service accessibility and resident wellbeing, with Abdoun Al-Janoubi demonstrating superior accessibility and higher wellbeing compared to Al-Zahra. Key insights are illustrated, with data supporting the idea that enhanced urban service access improves quality of life. Safety and esthetics are critical factors, while comfort is less significant. Abdoun Al-Janoubi’s favorable attributes lead to higher wellbeing scores. Recommendations for urban planners include improving Al-Zahra’s infrastructure, enhancing esthetics, and optimizing public transport. Community organizations should promote social engagement, while local governments need to adjust zoning laws and upgrade public amenities.